Leveraging Social Network Data for Analytical CRM Strategies --- The Introduction of Social BI - Rosemann, Michael; Eggert, Mathias; Voigt, Matthias; Beverungen, Daniel (Proceedings of the 20$^{th}$ European Conference on Information Systems)

Hybrid functionals and GW approximation in the FLAPW method - Friedrich, Christoph; Betzinger, Markus; Schlipf, Martin; Blügel, Stefan; Schindlmayr, Arno (Journal of Physics: Condensed Matter)
We present recent advances in numerical implementations of hybrid functionals and the GW approximation within the full-potential linearized augmented-plane-wave (FLAPW) method. The former is an approximation for the exchange–correlation contribution to the total energy functional in density-functional theory, and the latter is an approximation for the electronic self-energy in the framework of many-body perturbation theory. All implementations employ the mixed product basis, which has evolved into a versatile basis for the products of wave functions, describing the incoming and outgoing states of an electron that is scattered by interacting with another electron. It can thus be used for representing the nonlocal potential in hybrid functionals as well as the screened interaction and related quantities in GW calculations. In particular, the six-dimensional space integrals of the Hamiltonian exchange matrix elements (and exchange self-energy) decompose into sums over vector–matrix–vector products, which can be evaluated easily. The correlation part of the GW self-energy, which contains a time or frequency dependence, is calculated on the imaginary frequency axis with a subsequent analytic continuation to the real axis or, alternatively, by a direct frequency convolution of the Green function G and the dynamically screened Coulomb interaction W along a contour integration path that avoids the poles of the Green function. Hybrid-functional and GW calculations are notoriously computationally expensive. We present a number of tricks that reduce the computational cost considerably, including the use of spatial and time-reversal symmetries, modifications of the mixed product basis with the aim to optimize it for the correlation self-energy and another modification that makes the Coulomb matrix sparse, analytic expansions of the interaction potentials around the point of divergence at k=0, and a nested density and density-matrix convergence scheme for hybrid-functional calculations. We show CPU timings for prototype semiconductors and illustrative results for GdN and ZnO.

Strategy Planning of Collaborative Humanoid Soccer Robots based on Principle Solution - Low, Cheng; Aldemir, Mustafa; Aziz, Norheliena; Dumitrescu, Roman; Anacker, Harald (Proceedings of the 1st German-Malaysian Workshop, Hannover, 27. - 29. Jun. 2012)

Graph Transformation - 6th International Conference, ICGT 2012, Bremen, Germany, September 24-29, 2012, Proceedings

Energy Efficient Clustering using a Wake-up Receiver - Blanckenstein, Johannes; Klaue, Jirka; Karl, Holger (European Wireless 2012 - 18th European Conference 2012, April 18-20, 2012, Poznan, Poland.)

Efficiency of On-Path and Off-Path Caching Strategies in Information Centric Networks - Dräxler, Martin; Karl, Holger (2012 IEEE International Conference on Green Computing and Communications, Conference on Internet of Things, and Conference on Cyber, Physical and Social Computing, GreenCom/iThings/CPSCom 2012, Besancon, France, November 20-23, 2012)

Quantization techniques for accurate soft message combining - Volkhausen, Tobias; Schinköthe, Kai; Karl, Holger (2012 IEEE Wireless Communications and Networking Conference, WCNC 2012, Paris, France, April 1-4, 2012)

Efficient cooperative relaying in wireless multi-hop networks with commodity WiFi hardware - Volkhausen, Tobias; Dridger, Kornelius; S. Lichte, Hermann; Karl, Holger (10th International Symposium on Modeling and Optimization in Mobile, Ad Hoc and Wireless Networks (WiOpt), Paderborn, Germany, May 14-18, 2012)

Model-Based Testing: Achievements and Future Challenges - Mlynarski, Michael; Güldali, Baris; Weißleder, Stephan; Engels, Gregor (Advances in Computers)
Software systems are part of our everyday life and they become more complex day by day. The ever-growing complexity of software and high quality requirements pose tough challenges to quality assurance. The quality of a software system can be measured by software testing. However, if manually done, testing is a time-consuming and error-prone task. Especially test case design and test execution are the most cost-intensive activities in testing. In the previous 20 years, many automation tools have been introduced for automating test execution by using test scripts. However, the effort for creating and maintaining test scripts remains. Model-based testing (MBT) aims at improving this part by systematizing and automating the test case design. Thereby, test cases or automatable test scripts can be generated systematically from test models. MBT is already known for several years, but it currently gains a great momentum due to advanced tool support and innovative methodological approaches. This chapter aims at giving an overview of MBT and summarizes recent achievements in MBT. Experiences with using the MBT approach are illustrated by reporting on some success stories. Finally, open issues and future research challenges are discussed.

Self-Organized Nanostructure Formation for Anti-Reflection Glass Surfaces - Achtelik, Jörn; Kemper, Ricarda M.; Sievers, Werner; Lindner, Jörg (MRS Proceedings)
Two methods to create biomimetic anti-reflection nanostructures in ordinary glass microscope object slides are presented. One technique is based on a nanosphere lithography process combined with physical vapour deposition of nickel and reactive ion etching (RIE). The other uses plasma induced dewetting of a smooth nickel surface. The amount of reflected light was measured and a method to simulate the reflectivity from an atomic force microscopy (AFM) topography scan of the glass surface is presented. The reflectivity for visible light at normal incidence was reduced to 20-50 % of the original value with both methods and the simulation gives results in good agreement to the measurement.

Optical properties of cubic GaN from 1 to 20 eV - Feneberg, Martin; Röppischer, Marcus; Cobet, Christoph; Esser, Norbert; Schörmann, Jörg; Schupp, Thorsten; As, Donat Josef; Hörich, Florian; Bläsing, Jürgen; Krost, Alois; Goldhahn, Rüdiger (Physical Review B)

Asynchronous Occlusion Culling on Heterogeneous PC Clusters for Distributed 3D Scenes - Suess, Tim; Koch, Clemens; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
We present a parallel rendering system for heterogeneous PC clusters to visualize massive models. One single, powerful visualization node is supported by a group of backend nodes with weak graphics performance. While the visualization node renders the visible objects, the backend nodes asynchronously perform visibility tests and supply the front end with visible scene objects. The visualization node stores only currently visible objects in its memory, while the scene is distributed among the backend nodes’ memory without redundancy. To efficiently compute the occlusion tests in spite of that each backend node stores only a fraction of the original geometry, we complete the scene by adding highly simplified versions of the objects stored on other nodes. We test our system with 15 backend nodes. It is able to render a ≈ 350,M polygons (≈ 8.5,GiB) large aircraft model with 20, to 30,fps and thus allows a walk-through in real-time.

Glaschick, Rainer, “Alan Turings Wirkung in Münster”, In: Mitteilungen der Deutschen Mathematiker-Vereinigung 20 (2012), 42–48 - Peckhaus, Volker (Mathematical Reviews)

The dynamics of prior entry in serial visual processing. - Hilkenmeier, Frederic; Scharlau, Ingrid; Weiß, Katharina; Olivers, Christian N. L. (Visual Cognition)
An attended stimulus reduces the perceptual latency of a later stimulus at the same location, leading to the intriguing finding that the perceived order between the two is often reversed. This prior-entry effect has been well established in a number of different cueing paradigms, mostly involving spatial attentional shifts. Here we assess the time-course of prior entry when all stimuli appear in rapid serial presentation at one location. Our findings indicate that the size of the attentional enhancement is strongly affected by the stimulus onset asynchrony between cue and target, with a rapid early peak, followed by decay. When task-irrelevant cues are used, the cueing effect on prior entry is short-lived and peaks as early as 50 ms. The benefit extends to about 100 ms when task-relevant cues are employed. These results fit with a straightforward computational model of transient attentional enhancement, peaking about 80 100 ms after stimulus detection. (PsycINFO Database Record (c) 20
Keywords: serial visual processing; prior entry dynamics; cueing paradigms; Cues; Visual Perception; Visual Search

Sovereign Risk and Bank-Specific CDS Pricing - Meine, Christian; Michalak, Tobias C.; Uhde, André
Employing time series of single-name CDS market spreads from 29 European banks located in the EU-12 plus Switzerland and the UK over the period from January 2004 through September 2010 this paper analyses the relationship between increasing sovereign risk and bank-specific CDS pricing. Results from calculating relative CDS spread deviations (model minus market spreads) initially reveal a price bubble in the European CDS market until the beginning of the financial crisis in mid-2007. From this point in time the gap narrows remarkably during the financial crisis and sovereign debt crisis period. Corresponding to these findings, the empirical analysis reveals a negative impact of sovereign risk on calculated CDS spread differentials indicating a spill-over effect between sovereign risk and bank risk and hence, a positive effect on bank-specific CDS pricing. Further analyses reveal that the perception of sovereign risk is not crisis- but country-dependent suggesting that bank-specific CDS market spreads may already include a premium to cover sovereign risk from PIIGS countries during the pre-crisis period in Europe.
Keywords: Sovereign risk; Structural credit risk models; bank-specific CDS pricing

Better be reactive at the beginning. Implications of the first seconds of an encounter for the tutoring style in human-robot-interaction - Pitsch, Karola; Lohan, Katrin Solveig; Rohlfing, Katharina; Saunders, Joe; Nehaniv, Chrystopher L.; Wrede, Britta (Proceedings of the 21TH IEEE International Symposium on Robot and Human Interactive Communication (RO-MAN 2012))
The paper investigates the effects of a robot’s “on-line” feedback during a tutoring situation with a human tutor. Analysis is based on a study conducted with an iCub robot that autonomously generates its feedback (gaze, pointing gesture) based on the system’s perception of the tutor’s actions using the idea of reciprocity of actions. Sequential micro-analysis of two opposite cases reveals how the robot’s behavior (responsive vs. non-responsive) pro-actively shapes the tutor’s conduct and thus co-produces the way in which it is being tutored. A dialogic and a monologic tutoring style are distinguished. The first 20 seconds of an encounter are found to shape the user’s perception and expectations of the system’s competences and lead to a relatively stable tutoring style even if the robot’s reactivity and appropriateness of feedback changes.

Nonlocal Imaging by Conditional Averaging of Random Reference Measurements - Luo, Kai Hong; Huang, Bo-Qiang; Zheng, Wei-Mou; Wu, Ling-An (Chinese Physics Letters)

Textural analysis of optical scattering for identification of cancer in breast surgical specimens - Eguizabal, Alma; Laughney, Ashley M.; Garcia-Allende, P. Beatriz; Krishnaswamy, Venkataramanan; Wells, Wendy A.; Paulsen, Keith D.; Pogue, Brian W.; Lopez-Higuera, Jose M.; Conde, Olga M. (IEEE 9th International Symposium on Biomedical Imaging)
Textural analysis of tissue scattering images is proposed for healthy versus tumor discrimination. Scattering center density varies from normal to tumor tissues and this variation is translated into different textures in the scattering power map. Adipose tissue shows low autocorrelation values while tumor tissues present higher entropies than normal tissue. Consequently, a combination of autocorrelation and entropy values allows ready tissue discrimination by a supervised linear classifier. The proposed approach has been validated over a set of 29 breast tissue samples achieving a sensitivity of 73.59% and specificity of 82.40%.

ICA-guided delineation of breast cancer pathology - Eguizabal, Alma; Laughney, Ashley M.; Garcia-Allende, P. Beatriz; Krishnaswamy, Venkataramanan; Wells, Wendy A.; Paulsen, Keith D.; Pogue, Brian W.; Lopez-Higuera, Jose M.; Conde, Olga M. (IEEE 9th International Symposium on Biomedical Imaging)
A surgeon-guided independent component analysis from optical reflectance measurements is proposed for breast tumor delineation. Independent Component Analysis is first applied to extract the most relevant features from local measures of broadband reflectance and then a tumor probability indicator is obtained and provided utilizing surgeon assistance to resolve the inherent ambiguities in the independent component calculation. A set of 29 breast tissue samples have been diagnosed achieving a sensitivity of 90.57%, and specificity of 93.98%.

Diva – Die Inszenierung der übermenschlichen Frau. Interdisziplinäre Untersuchungen zu einem kulturellen Phänomen des 19. und 20. Jahrhunderts. Hrsg. von Rebecca Grotjahn, Dörte Schmidt und Thomas Seedorf. Schliengen: Edition Argus 2011. 275 S., Abb., Nbsp. (Forum Musikwis-senschaft. Band 7.) - Tumat, Antje (Die Musikforschung)

Mesoporöse Silica - Moderne Funktionsmaterialien im Chemieunterricht - Wilke, Timm; Haffer, Stefanie; Tiemann, Michael; Waitz, Thomas (CHEMKON)
Poröse Funktionsmaterialien wie halbleitende Metalloxide, Kohlenstoff-Formen oder auch Silica werden aktuell von verschiedenen Wissenschaftsdisziplinen intensiv für Bereiche der Energiespeicherung, Sensorik, Katalyse und Stofftrennung erforscht. Im Beitrag werden schwerpunktmäßig geordnet-mesoporöse Silica-Materialien behandelt, die seit etwa 20 Jahren synthetisch zugänglich sind. Neben den Grundlagen der Herstellung über ein Templat-Verfahren werden im Beitrag auch drei Experimente vorgestellt, die im Chemieunterricht oder Schülerlabor durchgeführt werden können. Zudem wird gezeigt, dass sich verschiedene Aspekte aus dem Kompetenzbereich Fachwissen mit Hilfe des Themas „Mesoporöse Silica“ miteinander vernetzen lassen.

Die Ordnung der (Nicht)Orte. Kampnagel und Kreativwirtschaft - Degeling, Jasmin (Performing Politics. Politisch Kunst machen nach dem 20. Jahrhundert)

Sovereign risk and bank-specific CDS pricing - Uhde, André; Michalak, Tobias; Meine, Christian
Employing time series of single-name CDS market spreads from 29 European banks located in the EU-12 plus Switzerland and the UK over the period from January 2004 through September 2010 this paper analyses the relationship between increasing sovereign risk and bank-specific CDS pricing. Results from calculating relative CDS spread deviations (model minus market spreads) initially reveal a price bubble in the European CDS market until the beginning of the financial crisis in mid-2007. From this point in time the gap narrows remarkably during the financial crisis and sovereign debt crisis period. Corresponding to these findings, the empirical analysis reveals a negative impact of sovereign risk on calculated CDS spread differentials indicating a spill-over effect between sovereign risk and bank risk and hence, a positive effect on bank-specific CDS pricing. Further analyses reveal that the perception of sovereign risk is not crisis- but country-dependent suggesting that bank-specific CDS market spreads may already include a premium to cover sovereign risk from PIIGS countries during the pre-crisis period in Europe.

Der Kuss, ein Päckchen und der Spiegel. Zur Rhetorik der Authentizität - oder wer sieht wen eigentlich wie an? - Janus, Richard (Scripts, Fiktionen, Konstruktionen. Theologische, kirchliche und popkulturelle Anmerkungen zu Reality-TV und gefühlsechtem Leben)

1.-3. Johannesbrief - Janus, Richard (Religionspädagogischer Kommentar zur Bibel)

Plasma-polymerized HMDSO coatings to adjust the silver ion release properties of Ag/polymer nanocomposites - Alissawi, N.; Peter, T.; Strunskus, T.; Ebbert, Christoph; Grundmeier, Guido; Faupel, F. (JOURNAL OF NANOPARTICLE RESEARCH)
In the current work, we study the silver ion release potential and the water uptake through a SiOxCyHz-polymer which is grown from the precursor hexamethyldisiloxane (HMDSO) in radiofrequency (RF) plasma. These layers were deposited on top of two dimensional (2D) ensembles of silver nanoparticles (AgNPs) with nominal thickness of 2 nm on a 20 nm RF-sputtered polytetrafluoroethylene (PTFE) thin film. The composition of the plasma-polymerized HMDSO barriers was varied by changing the oxygen flow during the polymerization process and their thickness was varied as well. Morphology and optical properties of the nanocomposites were investigated using transmission electron microscopy (TEM) and UV-Visible spectroscopy (UV-Vis), respectively. The concentration of the silver ions released from the nanocomposites after immersion in water for several time intervals was measured using inductively coupled plasma mass spectrometry (ICP-MS). Contact angle analysis and electrochemical impedance spectroscopy (EIS) measurements were also performed and results show a strong dependence of the coatings properties and their water uptake on the oxygen content in the coating films and their thickness. Plasma polymerization with increasing the oxygen flow leads to the formation of more hydrophilic thin films with a higher Ag ion release potential. Increasing the thickness of the coatings reduced the amount of the released ions and the rate of the release process was slowed down. This indicates that by tailoring the structure and the thickness of the plasma-polymerized coating films, one can tune the silver ion release properties of Ag/polymer nanocomposites.

Energetische Optimierung eines Mehrmotorenantriebssystems für Kautschukinnenmischer - Hölscher, Christian; Michaelis, Stefanie; Strop, Malte; Zimmer, Detmar

Vorgehensmodelle 2013: Vorgehensmodelle - Anspruch und Wirklichkeit - Proceedings der 20. Tagung der Fachgruppe Vorgehensmodelle im Fachgebiet Wirtschaftsinformatik (WI-VM) der Gesellschaft für Informatik e.V., Lörrach (Germany)

Konzeption modellbasierter Benutzungsschnittstellen für verteilte Selbstbedienungssysteme - Yigitbas, Enes; Gerth, Christian; Sauer, Stefan (Informatik 2013, 43. Jahrestagung der Gesellschaft für Informatik e.V. (GI), Informatik angepasst an Mensch, Organisation und Umwelt, 16.-20. September 2013, Koblenz, Deutschland)

Modelling the friction contact in an inertia motor - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Journal of Intelligent Material Systems and Structures)
Piezoelectric inertia motors, also known as stickslip drives or (smooth) impact drives, use the inertia of a body to drive it by a friction contact in small steps, in the majority of motors composed of a stick phase and a slip phase between the friction partners. For optimizing inertia motors, it is important to understand the friction contact correctly and to measure its properties appropriately. This contribution presents experimental set-ups for measuring the contact force, friction force and relative displacement in an actual inertia motor with a dry friction contact and numerical simulations of the motor operation. The motor uses a pre-stressed multilayer actuator with a displacement in the range of 20 $μ$ m. It is shown that a previously postulated condition for the applicability of simple kinetic friction models is well fulfilled for the investigated motor. The friction contact in the motor is simulated using different kinetic friction models. The input for the friction models is the measured motion of the rod. The models qualitatively reproduce the measured motion but show quantitative deviations varying with frequency. These can be explained by vibrations of the driving rod that are experimentally investigated.
Keywords: Actuator; friction; motor; piezoelectric

How many attackers can selfish defenders catch? - Mavronicolas, Marios; Monien, Burkhard; Papadopoulou Lesta, Vicky (Discrete Applied Mathematics)
In a distributed system with attacks and defenses, both attackers and defenders are self-interested entities. We assume a reward-sharing scheme among interdependent defenders; each defender wishes to (locally) maximize her own total fair share to the attackers extinguished due to her involvement (and possibly due to those of others). What is the maximum amount of protection achievable by a number of such defenders against a number of attackers while the system is in a Nash equilibrium? As a measure of system protection, we adopt the Defense-Ratio (Mavronicolas et al., 2008)[20], which provides the expected (inverse) proportion of attackers caught by the defenders. In a Defense-Optimal Nash equilibrium, the Defense-Ratio matches a simple lower bound.We discover that the existence of Defense-Optimal Nash equilibria depends in a subtle way on how the number of defenders compares to two natural graph-theoretic thresholds we identify. In this vein, we obtain, through a combinatorial analysis of Nash equilibria, a collection of trade-off results:• When the number of defenders is either sufficiently small or sufficiently large, Defense-Optimal Nash equilibria may exist. The corresponding decision problem is computationally tractable for a large number of defenders; the problem becomes NPNP-complete for a small number of defenders and the intractability is inherited from a previously unconsidered combinatorial problem in Fractional Graph Theory.• Perhaps paradoxically, there is a middle range of values for the number of defenders where Defense-Optimal Nash equilibria do not exist.

245 GHz subharmonic receivers in SiGe - Mao, Yanfei; Schmalz, Klaus; Borngräber, Johannes; Scheytt, Christoph (2013 IEEE Radio Frequency Integrated Circuits (RFIC) Symposium)
Two subharmonic receivers for 245 GHz spectroscopy sensor applications in the 245 GHz ISM band have been proposed. One receiver consists of an 2nd APDP (antiparallel diode pair) passive SHM (subharmonic mixer), a 120 GHz push-push VCO with 1/64 divider, and a 120 GHz PA (power amplifier). The other consists of a single-ended four-stage CB (common base) LNA, an 2 nd APDP passive SHM, an IF amplifier, a 120 GHz push-push VCO with 1/64 divider, and a 120 GHz PA. The receivers are fabricated in a SiGe:C BiCMOS technology with f T /f max =300/500 GHz. The measured conversion gain are -17 dB rsp. 10.6 dB at 245 GHz with 3-dB bandwidths of 13 GHz rsp. 14 GHz, and the single-side band noise figure are 17 dB rsp. 20 dB; the two receivers dissipates a power of 213 mW and 312 mW, respectively.

A 240 GHz Direct Conversion IQ Receiver in 0.13 µm SiGe BiCMOS technology - Elkhouly, Mohamed; Mao, Yanfei; Meliani, Chafik; Ellinger, Frank; Scheytt, Christoph (2013 IEEE Radio Frequency Integrated Circuits (RFIC) Symposium,)
A 240 GHz direct conversion IQ receiver manufactured in 0.13 SiGe BiCMOS technology with f T /f max of 300/500 GHz is presented. The receiver consists of a four stage LNA, an active power divider, an LO IQ generation network, and direct down-conversion fundamental mixers. The integrated IQ receiver yields a conversion gain of 18 dB, an 18 dB simulated DSB NF, and a 3 dB bandwidth of 25 GHz. The required 245 GHz LO power is in the order of -10 dBm. The receiver exhibits an IQ amplitude and phase imbalance of 1 dB and 3° respectively. It draws 135 mA from the 3.5 V supply and 20 mA from 2 V.

Meier, Simon: Gesprächsideale. Normative Gesprächsreflexion im 20. Jahrhundert - Ptashnyk, Stefaniya (GERMANISTIK, Heft 1-2, 2014)

Themenheft: Die Börse als Ort von Ressourcenkonflikten im 19. und 20. Jahrhundert (Bankhistorisches Archiv)

An Energy-Efficient Heuristic for Hard Real-Time System on Multi-Core Processors - He, Da; Müller, Wolfgang (Proceedings of the International Conference on Applied Computing (AC))
In the electronic system development, energy consumption is clearly becoming one of the most important design concerns. From the system level point of view, Dynamic Power Management (DPM) and Dynamic Voltage and Frequency Scaling (DVFS) are two mostly applied techniques to adjust the tradeoff between the performance and power dissipation at runtime. In this paper, we study the problem of combined application of both techniques with regard to hard real-time systems running on cluster-based multi-core processors. To optimize the processor energy consumption, a heuristic based on simulated annealing with efficient termination criterion is proposed. The experiment results show that the proposed algorithm outperforms the existing approaches in terms of the energy reduction.
Keywords: Dynamic Power Management; Dynamic Voltage and Frequency Scaling; Hard Real-Time; Multi-core Processor

20 krad/s endless optical polarisation and phase control - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D. (ELECTRONICS LETTERS)

20-Gb/s PDM-RZ-DPSK Transmission With 40 krad/s Endless Optical Polarization Tracking - Koch, Benjamin; Noé, Reinhold; Sandel, David; Mirvoda, Vitali; Omar, Jan; Puntsri, Kidsanapong (IEEE PHOTONICS TECHNOLOGY LETTERS)

20-Gb/s PDM-RZ-DPSK Transmission With 40 krad/s Endless Optical Polarization Tracking - Koch, Benjamin; Noé, Reinhold; Sandel, David; Mirvoda, Vitali; Omar, Jan; Puntsri, Kidsanapong (IEEE Photonics Technology Letters)

20-Gb/s PDM-RZ-DPSK Transmission With 40 krad/s Endless Optical Polarization Tracking - Koch, Benjamin; Noé, Reinhold; Sandel, David; Mirvoda, Vitali; Omar, Jan; Puntsri, Kidsanapong (IEEE PHOTONICS TECHNOLOGY LETTERS)

Linear classifier and textural analysis of optical scattering images for tumor classification during breast cancer extraction - Eguizabal, Alma; Laughney, Ashley M.; Garcia-Allende, P. Beatriz; Krishnaswamy, Venkataramanan; Wells, Wendy A.; Paulsen, Keith D.; Pogue, Brian W.; Lopez-Higuera, Jose; Conde, Olga M. (SPIE Photonics West BIOS, VIII Biomedical Applications of Light Scattering)
Texture analysis of light scattering in tissue is proposed to obtain diagnostic information from breast cancer specimens. Light scattering measurements are minimally invasive, and allow the estimation of tissue morphology to guide the surgeon in resection surgeries. The usability of scatter signatures acquired with a micro-sampling reflectance spectral imaging system was improved utilizing an empirical approximation to the Mie theory to estimate the scattering power on a per-pixel basis. Co-occurrence analysis is then applied to the scattering power images to extract the textural features. A statistical analysis of the features demonstrated the suitability of the autocorrelation for the classification of notmalignant (normal epithelia and stroma, benign epithelia and stroma, inflammation), malignant (DCIS, IDC, ILC) and adipose tissue, since it reveals morphological information of tissue. Non-malignant tissue shows higher autocorrelation values while adipose tissue presents a very low autocorrelation on its scatter texture, being malignant the middle ground. Consequently, a fast linear classifier based on the consideration of just one straightforward feature is enough for providing relevant diagnostic information. A leave-one-out validation of the linear classifier on 29 samples with 48 regions of interest showed classification accuracies of 98.74% on adipose tissue, 82.67% on non-malignant tissue and 72.37% on malignant tissue, in comparison with the biopsy H and E gold standard. This demonstrates that autocorrelation analysis of scatter signatures is a very computationally efficient and automated approach to provide pathological information in real-time to guide surgeon during tissue resection.

Direct identification of breast cancer pathologies using blind separation of label-free localized reflectance measurements - Eguizabal, Alma; Laughney, Ashley M.; Garcia-Allende, P. Beatriz; Krishnaswamy, Venkataramanan; Wells, Wendy A.; Paulsen, Keith D.; Pogue, Brian W.; Lopez-Higuera, Jose M.; Conde, Olga M. (Biomed. Opt. Express)
Breast tumors are blindly identified using Principal (PCA) and Independent Component Analysis (ICA) of localized reflectance measurements. No assumption of a particular theoretical model for the reflectance needs to be made, while the resulting features are proven to have discriminative power of breast pathologies. Normal, benign and malignant breast tissue types in lumpectomy specimens were imaged ex vivo and a surgeon-guided calibration of the system is proposed to overcome the limitations of the blind analysis. A simple, fast and linear classifier has been proposed where no training information is required for the diagnosis. A set of 29 breast tissue specimens have been diagnosed with a sensitivity of 96% and specificity of 95% when discriminating benign from malignant pathologies. The proposed hybrid combination PCA-ICA enhanced diagnostic discrimination, providing tumor probability maps, and intermediate PCA parameters reflected tissue optical properties.

Formation and Properties of TiSi2 as Contact Material for High-Temperature Thermoelectric Generators - Assion, Fabian; Schönhoff, Marcel; Hilleringmann, Ulrich (MRS Proceedings)
ABSTRACT Thermoelectric generators (TEG) are capable of transforming waste heat directly into electric power. With higher temperatures the yield of the devices rises which makes high-temperature contact materials important. The formation of titanium disilicide (TiSi 2 ) and its properties were analyzed and optimized for the use in TEG. Depending on a direct or an indirect transformation into the C54 crystal structure the process forms a layer with a resistivity of 20-22 μΩcm. Process gases influence the resistivity and result in difference of 20 %. The growing rate of TiSi 2 on silicon dioxide was determined; it shows a strong dependence on the used atmosphere and temperature. A maximum overgrowing length of 30 μm was found.
Keywords: General Engineering

Medienpädagogische Qualifikation für Lehrkräfte - Herzig, Bardo; Martin, A. (Medien – Bildung - Schule, Dokumentation der ersten Netzwerktagung Medienkompetenz Sachsen-Anhalt, Halle (Saale), 19. und 20. September 2011)

Wenn der Konzertsaal zur Kirche wird. Mendelssohn Bartholdy, Schleiermacher und die Wiederaufführung der Matthäuspassion 1829 - Janus, Richard (Musik in Religion - Religion in Musik)

Invokavit: Was ist Glück? - Janus, Richard (...und den Mond als Licht für die Nacht. Andachten zur Nacht im Kirchenjahr)

Bernd Zymner: 100 Jahre Auferstehungskirche in Brakel. "eine neue, völlig eigene Kirche, die evangelischen Begriffen entspricht, Brakel 2012 - Janus, Richard (Paderborner Historische Mitteilungen)

HiBISCuS: Hypergraph-Based Source Selection for SPARQL Endpoint Federation - Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: Trends and Challenges - 11th International Conference, ESWC 2014, Anissaras, Crete, Greece, May 25-29, 2014. Proceedings)

Unsupervised Link Discovery through Knowledge Base Repair - Ngonga Ngomo, Axel-Cyrille; Ahmed Sherif, Mohamed; Lyko, Klaus (The Semantic Web: Trends and Challenges - 11th International Conference, ESWC 2014, Anissaras, Crete, Greece, May 25-29, 2014. Proceedings)

LinkLion: A Link Repository for the Web of Data - Nentwig, Markus; Soru, Tommaso; Ngonga Ngomo, Axel-Cyrille; Rahm, Erhard (The Semantic Web: ESWC 2014 Satellite Events - ESWC 2014 Satellite Events, Anissaras, Crete, Greece, May 25-29, 2014, Revised Selected Papers)

Hybrid Acquisition of Temporal Scopes for RDF Data - Rula, Anisa; Palmonari, Matteo; Ngonga Ngomo, Axel-Cyrille; Gerber, Daniel; Lehmann, Jens; Bühmann, Lorenz (The Semantic Web: Trends and Challenges - 11th International Conference, ESWC 2014, Anissaras, Crete, Greece, May 25-29, 2014. Proceedings)

conTEXT - Lightweight Text Analytics Using Linked Data - Khalili, Ali; Auer, Sören; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: Trends and Challenges - 11th International Conference, ESWC 2014, Anissaras, Crete, Greece, May 25-29, 2014. Proceedings)

Cross-Document Coreference Resolution Using Latent Features - Ngonga Ngomo, Axel-Cyrille; Röder, Michael; Usbeck, Ricardo (Proceedings of the Second International Workshop on Linked Data for Information Extraction {(LD4IE} 2014) co-located with the 13th International Semantic Web Conference {(ISWC} 2014), Riva del Garda, Italy, October 20, 2014)

Time-efficient execution of bounded Jaro-Winkler distances - Dreßler, Kevin; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 9th International Workshop on Ontology Matching collocated with the 13th International Semantic Web Conference {(ISWC} 2014), Riva del Garda, Trentino, Italy, October 20, 2014)

Proceedings of the 9th International Workshop on Ontology Matching collocated with the 13th International Semantic Web Conference (ISWC 2014), Riva del Garda, Trentino, Italy, October 20, 2014

Vorausschau und Technologieplanung. 10. Symposium für Vorausschau und Technologieplanung, Heinz Nixdorf Institut, 20. und 21. November 2014 - Gausemeier, Jürgen

A Framework for the Computer-aided Planning and Optimisation of Manufacturing Processes for Components with Functional Graded Properties - Biermann, Dirk; Gausemeier, Jürgen; Heim, Hans-Peter; Hess, Stefan; Petersen, Marcus; Ries, Angela; Wagner, T (Proceedings of PPS-29. The 29th International Conference of the Polymer Processing Society - Conference Papers)
n this contribution a framework for the computer-aided planning and optimisation of functional graded components is presented. The framework is divided into three modules - the "Component Description", the "Expert System" for the synthetisation of several process chains and the "Modelling and Process Chain Optimisation". The Component Description module enhances a standard computer-aided design (CAD) model by a voxel-based representation of the graded properties. The Expert System synthesises process steps stored in the knowledge base to generate several alternative process chains. Each process chain is capable of producing components according to the enhanced CAD model and usually consists of a sequence of heating-, cooling-, and forming processes. The dependencies between the component and the applied manufacturing processes as well as between the processes themselves need to be considered. The Expert System utilises an ontology for that purpose. The ontology represents all dependencies in a structured way and connects the information of the knowledge base via relations. The third module performs the evaluation of the generated process chains. To accomplish this, the parameters of each process are optimised with respect to the component specification, whereby the result of the best parameterisation is used as representative value. Finally, the process chain which is capable of manufacturing a functionally graded component in an optimal way regarding to the property distributions of the component description is presented by means of a dedicated specification technique.

Handling TSO in Mechanized Linearizability Proofs - Travkin, Oleg; Wehrheim, Heike (Hardware and Software: Verification and Testing - 10th International Haifa Verification Conference, HVC 2014, Haifa, Israel, November 18-20, 2014. Proceedings)

World Cultural Heritage: Cultural Identity and the War on Works of Art. Introduction, Sketch of Problems and Objects - Seng, Eva- Maria (The Challenge of the Object. Section 6, The Proceedings of the 33. International Congress in the History of Art. Nuremberg, 15.-20. July 2012. Comité International d’Histoire de l’Art, CIHA, Bd. 2)

Feature models supporting trade-off decisions in early mechatronic systems design - Kühn, Arno; Bremer, Christian; Dumitrescu, Roman; Gausemeier, Jürgen (NordDesign 2014, Espoo, Finnland, 27. - 29. Aug. 2014)

RSDL workbench results for OAEI 2014 - Schwichtenberg, Simon; Gerth, Christian; Engels, Gregor (Proceedings of the 9th International Workshop on Ontology Matching collocated with the 13th International Semantic Web Conference (ISWC 2014), Riva del Garda, Trentino, Italy, October 20, 2014.)

Vertrauensarbeit nach dem Bankrott: Die Internationale Finanzkommission für Griechenland zwischen 1898 und 1914 - Schönhärl, Korinna (Finanzpolitik und Schuldenkrisen 16.-20. Jahrhundert)

Individuation in Adults’ Family Interactions: An Observational Study - Buhl, Heike M.; Scholwin, Berit; Noack, Peter (Journal of Adult Development)
The study investigates the status of individuation in adult child–parent relationships expressed in verbal interactions, as well as considering verbal behavior as a means to individuate. A sample of 41 German adult children aged 20–45 years and their 39 mothers and 19 fathers were videotaped in dyadic conflict discourse. The interactions were coded in their entirety, and scales were allocated to the factor connectedness, individuality, and conflict. Group comparisons show that mothers and fathers do not differ. Middle-aged adults interacted in a more individuated manner than young adults. Their mothers interacted in a way that was more connected and less conflictual than mothers in interactions with younger adults; their fathers, on the other hand, interacted more conflictual. The behavior of adult children and their parents did not differ and so expressed a high amount of behavioral symmetry. Associations between the self-report about the relationship and family members’ behavior point to verbal interaction as a means for negotiating the relationship.
Keywords: Life-span and Life-course Studies; Developmental and Educational Psychology; Experimental and Cognitive Psychology

Design and Measurement Techniques for an 80 Gb/s 1-Tap Decision Feedback Equalizer - Awny, Ahmed; Möller, Lothar; Junio, Josef; Scheytt, Christoph; Thiede, Andreas (IEEE JOURNAL OF SOLID-STATE CIRCUITS)
A millimeter wave frequency mixed-signal design of a 1-tap half-rate look-ahead decision feedback equalizer for 80 Gb/s short-reach optical communication systems is presented. On-wafer tests are developed to determine the maximum operating bit rate of the equalizer. Results are also presented for intersymbol interference mitigation at 80 Gb/s for a 20 GHz bandwidth-limited channel. Further improvements on the architecture of the 80 Gb/s equalizer are discussed and used in the design and on-wafer measurement of a 110 Gb/s equalizer. The equalizers are designed in a 0.13 μm SiGe:C BiCMOS technology. The 80 and 110 Gb/s versions dissipate 4 and 5.75 W, respectively and occupy 2 and 2.56 mm 2 , respectively.

Stimmbesitzer und Sängerdarsteller. Die Inszenierung des Singens auf der Musiktheater-Bühne in den ersten Jahrzehnten des 20. Jahrhunderts - Grotjahn, Rebecca (Blickpunkt Bühne. Musiktheater in Deutschland von 1900 bis 1950)

Impuls und Design - Friedensklänge aus dem 20. Jahrhundert. Zum 100. Geburtstag von Andrzej Panufnik - Schroeter-Wittke, Harald (Praktische Theologie)

Anodized Aluminum as Effective and Cheap Alternative Substrate for Thermoelectric Generators - Assion, F.; Geneiß, V.; Schönhoff, M.; Hedayat, C.; Hilleringmann, Ulrich (Proceedings of the 11th European Conference on Thermoelectrics)
The wide usage of thermoelectric generators (TEG) is still blocked by very high product costs. This paper presents anodized aluminum (Al) as an effective and cheap alternative for ceramics like alumina (Al2O3) or aluminum nitride (AlN). Al has a significantly higher thermal conductivity as both named ceramics. In addition, the lower thermal stability of Al is still high enough to work with bismuth telluride based modules, which are most common. To show the advantages of the changed substrate, finite element method (FEM) simulations were performed. These simulations show that by changing the cold side substrate material the temperature drop across the substrate is reduced by 60 K. This correlates to a theoretical power gain of more than 20 {%}. Furthermore, Al can be shaped much easier than a ceramic material. The biggest advantage is obviously the price. Anodized Al is around twenty times cheaper than Al2O3. To demonstrate the easy fabrication of the proposed substrate, samples were prepared only with widely used processes like those used for conventional printed circuit boards.

Hydrogen Effects in ECR-Etching of 3C-SiC(100) Mesa Structures - Hiller, Lars; Stauden, Thomas; Kemper, Ricarda M.; Lindner, Jörg; As, Donat J.; Pezoldt, Jörg (Materials Science Forum)
An anisotropic etching process for mesa structures using fluorinated plasma with hydrogen addition was developed in an electron cyclotron resonance setup. The evolution of the mesa morphology was studied in dependence on the gas composition, the applied bias and the pressure. The achieved side wall slope approached 90° with a negligible trenching. The aspect ratios of the fabricated structure in the developed residue free ECR plasma etching process were between 5 and 20.

„Partizipation – bildkompetent und interkulturell“. Bericht über eine Tagung des BDK Landesverbandes Nordrhein-Westfalen am 29. Januar 2014 - Pauls, Karina (BDK-Mitteilungen)

Darf man Kunstwerke zu Illustrationen machen? Die Luther-Abbildungen in der Schulbuchreihe Kursbuch für Sek. I - Janus, Richard (Religiöse Sozialisation, Erziehung und Bildung in historischer Perspektive. Arbeitsfelder der Religionspädagogik)

Vom Apophthegma zum Tweed. Minimalisierung als emergente Identitäts- und Weltkonstruktion - Janus, Richard (Social Media, christliche Religiosität und Kirche. Studien zur Praktischen Theologie mit religionspädagogischem Schwerpunkt)

Online-Optimierung zur Festlegung von Bestellzeitpunkten in der Losgrößenfertigung - Dangelmaier, Wilhelm (Schenk, Michael;Zadek, Hartmut;Müller, Gerhard;Richter, Klaus;Seidel, Holger (Hrsg.): 20. Magdeburger Logistiktage "Sichere und nachhaltige Logistik")

Vorausschau und Technologieplanung. 11. Symposium für Vorausschau und Technologieplanung, Heinz Nixdorf Institut, 29. und 30. Oktober 2015 - Gausemeier, Jürgen

On the bipolar charge distribution used for mobility particle sizing: Theoretical considerations - Tigges, L.; Jain, A.; Schmid, Hans-Joachim (Journal of Aerosol Science)
An essential part of mobility particle size spectroscopy is the prediction of the aerosol charge distribution in a highly concentrated bipolar ion environment. This charge distribution can be readily calculated, but is depending on several environmental conditions. These influences are investigated theoretically. The first part of this work deals with a sensitivity analysis using the Fuchs model (Fuchs, 1963) to determine the variation of the resulting charge distributions depending on the input parameters. It is demonstrated, that the main influencing variable is the difference between the positive and negative ion mobility. A sensitivity analysis reveals that a reasonable variation of the ion mobilities may lead to variations of the particle density distribution up to±20%. The second part investigates the evolution of the charge distribution along the tubing downstream of the bipolar charger exit starting with equal ion concentrations for positive and negative ions. Due to wall losses depending on ion mobility a non-equilibrium charge distribution is developing along the plumbing. The evolution of the particle charge distribution is determined using a coupled population balance model. Even though the non-equilibrium character is clearly shown, it turns out that this effect is negligible at conditions typical for particle size measurements.

20 Jahre Lernen mit dem World Wide Web - Technik und Bildung im Dialog - Keil, Reinhard; Harald, Selke

WebArena - R {\ "a} spacious structures for ü r the learning locations of the future - Winkelnkemper, Felix; Oberhoff, Andreas

20 years of learning with the World Wide Web - technology and education in dialogue

Learn with, through and {\ "about the WWW - Keil, Reinhard; Selke, Harald

Virtual knowledge {\ "a} ume - From the presentation of content to virtual learning ä tten - Keil, Reinhard; Selke, Harald

Influence of Material Properties on the Bond Strength of a Hybrid Part Consisting of Composite Sheet and Short-Fiber Thermoplastic - Moritzer, Elmar; Budde, C. (20. Symposium Verbundwerkstoffe und Werkstoffverbunde)

August Grisebach und die Neuausrichtung der deutschen Kunstgeschichte Anfang des 20. Jahrhunderts - Seng, Eva- Maria (Die Universität Breslau in der europäischen Kultur des 19. und 20. Jahrhunderts, in: Wroclaw University in the European Culture of 19th and 20th Centuries. Papers from the International Scientific Conference, Wroclaw 2011)

On Network Application representation and controller independence in {SDN - A. Aranda-Gutierrez, Pedro; Karl, Holger; Rojas, Elisa; Leckey, Alec (2015 European Conference on Networks and Communications, EuCNC 2015, Paris, France, June 29 - July 2, 2015)

Towards 100 Gbps Wireless Communication in THz Band with PSSS Modulation: A Promising Hardware in the Loop Experiment - KrishneGowda, Karthik; Messinger, Tobias; Wolf, Andreas; Kraemer, Rolf; Kallfass, Ingmar; Scheytt, Christoph (ICUWB 2015)
Terahertz frequency band of 0.06 - 10 THz is especially interesting for ultra-high-speed wireless communication to achieve data rates of 100 Gbps or higher. To accommodate this demand, advanced terahertz signal processing techniques need to be investigated. Parallel Sequence Spread Spectrum (PSSS) is a physical layer (PHY) baseband technology that seems to be suited for being used for ultra-high speed wireless communication since the receiver architecture is especially simple and can be implemented almost completely in analog hardware. In this paper, a PSSS modulated signal at a chip rate of 20 Gcps with a spectral efficiency of (only) 1 bit/s/Hz is transmitted using a linearity limited 240 GHz wireless frontend. PSSS transceiver models are realized offline in MATLAB/Simulink. The PSSS transmitter generates the PSSS modulated symbols that are loaded onto an Arbitrary Waveform generator (AWG) and then transmitted using the available 240 GHz wireless frontend. A Digital Storage Oscilloscope (DSO) samples and stores the received signal. The PSSS receiver performs synchronization, channel estimation and demodulation. For a coded data rate of 20 Gbps, an eye opening of 40% and a BER of 5.4·10 -5 has been measured. These results are highly promising to achieve data rates of up to 100 Gbps with PSSS modulation using a RF-frontend having higher linear operating range and thus allowing increasing the bandwidth efficiency to 4 b/s/Hz.

System Design and Simulation of a PSSS Based Mixed Signal Transceiver for a 20 Gbps Bandwidth Limited Communication Link - Javed, Abdul Rehman; Scheytt, Christoph (1st URSI Atlantic Radio Science Conference (URSI AT-RASC 2015))
Parallel Sequence Spread Spectrum (PSSS) is a physical layer baseband technology wherein parallel data streams are transmitted simultaneously by spreading them using orthogonal codes. PSSS was selected for the wireless sensor network standard IEEE802.15.4-2006 to increase data rate and improve performance in fading channels for frequency bands below 1 GHz. Since then it has gained interest for both wireless and wired communication links.

„Leider sind wir bankrott“. Zahlungsausfälle in der Geschichte Griechenlands im 19. und 20. Jahrhundert - Schönhärl, Korinna (Die Krise in Griechenland. Ursprünge, Verlauf, Folgen)

20 years of learning with the World Wide Web - technology and education in dialogue

FELIX: a High-Throughput Network Approach for Interfacing to Front End Electronics for ATLAS Upgrades - Anderson, J; Borga, A; Boterenbrood, H; Chen, H; Chen, K; Drake, G; Francis, D; Gorini, B; Lanni, F; Lehmann Miotto, G; Levinson, L; Narevicius, J; et al. (Journal of Physics: Conference Series)
The ATLAS experiment at CERN is planning full deployment of a new unified optical link technology for connecting detector front end electronics on the timescale of the LHC Run 4 (2025). It is estimated that roughly 8000 GBT (GigaBit Transceiver) links, with transfer rates up to 10.24 Gbps, will replace existing links used for readout, detector control and distribution of timing and trigger information. A new class of devices will be needed to interface many GBT links to the rest of the trigger, data-acquisition and detector control systems. In this paper FELIX (Front End LInk eXchange) is presented, a PC-based device to route data from and to multiple GBT links via a high-performance general purpose network capable of a total throughput up to O(20 Tbps). FELIX implies architectural changes to the ATLAS data acquisition system, such as the use of industry standard COTS components early in the DAQ chain. Additionally the design and implementation of a FELIX demonstration platform is presented and hardware and software aspects will be discussed.

An Overview of Topic Discovery in Twitter Communication through Social Media Analytics - Chinnov, Andrey; Kerschke, Pascal; Meske, Christian; Stieglitz, Stefan; Trautmann, Heike (Proceedings of the 20$^th$ Americas Conference on Information Systems (AMCIS ’15))
The need for automatic methods of topic discovery in the Internet grows exponentially with the amount of available textual information. Nowadays it becomes impossible to manually read even a small part of the information in order to reveal the underlying topics. Social media provide us with a great pool of user generated content, where topic discovery may be extremely useful for businesses, politicians, researchers, and other stakeholders. However, conventional topic discovery methods, which are widely used in large text corpora, face several challenges when they are applied in social media and particularly in Twitter – the most popular microblogging platform. To the best of our knowledge no comprehensive overview of these challenges and of the methods dedicated to address these challenges does exist in IS literature until now. Therefore, this paper provides an overview of these challenges, matching methods and their expected usefulness for social media analytics.

Tagungsbericht: Utopie & Alltag. Perspektiven auf Ideal und Praxis im 20. Jahrhundert, 23.04.2015 – 24.04.2015 Potsdam (gem. mit Janine Funke, geb. Noack) - Schmitt, Martin (H-Soz-Kult)

Unterbrochene Lektüre. Ein psaltertheologisches Pasticcio zur Unterbrechung als Leitkategorie einer religionspädagogischen Fachdidaktik - Janus, Richard (Theologie des Psalters)

Librettist Berlioz. Die ‚idée fixe‘ in Les Troyens und Berlioz’ Verhältnis zur Grand opéra Scribe’scher Prägung - Münzmay, Andreas (Von Gluck zu Berlioz - Die französische Oper zwischen Antikenrezeption und Monumentalität)
Wie arbeitete Berlioz als Librettist? Dass der Opernkomponist Berlioz sich auf Gluck und Spontini als Vorbilder berief, das heißt, dass sein das eigene Schaffen untermauernder Rückblick die moderne französische grand opéra seit den ausgehenden 1820er-Jahren gewissermaßen übersprang, ist schon angesichts der schieren Präsenz der Werke Aubers, Halévys und Meyerbeers auf den europäischen Spielplänen als sehr bewusst angewandte diskursive Strategie aufzufassen. Eine offene Frage ist dabei diejenige nach den eigentlichen poetologischen Funktionsgrundlagen dieses spezifisch Berlioz’schen Traditionsbezugs. So erscheint es lohnend, an dieser Stelle einen Schritt hinter den musikalischen Kompositionsprozess zurückzugehen zu dessen librettistisch-dramaturgischen Grundlegungen und zu fragen, inwieweit Berlioz – in seiner Funktion als sein eigener Librettist – den musiktheatralen Text (hier: im Sinne eines umfassenden, die medialen Ebenen Sprache, Musik, Bühne einschließenden Textbegriffs) so vorstrukturierte, dass er sein vom Mainstream der grand opéra seiner Zeit deutlich verschiedenes opernkompositorisches Konzept zu tragen vermochte. Betrifft Berlioz’ Orientierung an älteren Vorbildern der französischen Oper unbestritten die Wahl des antiken Sujets, so zielt sie aber, davon ausgehend und gleichzeitig darüber weit hinausgehend, auch auf eine Art Wiedergewinnung von Raum für die genuin musikalische Mitteilung. Berlioz erarbeitet sich dies in Abgrenzung zu jener Dramaturgie der modernen französischen Oper seiner Zeit, deren zentrale Errungenschaft die musiktheatrale Präsentation einer in realistischer Weise voranschreitenden, innerhalb des Werks geschlossenen Handlung war. Die Fragmentierung der Dramaturgie (im Sinne einer Auflösung des Primats der Stringenz der Intrige), die Berlioz dafür nicht nur in Kauf nimmt, sondern überaus gezielt betreibt, darf wohl gleichermaßen als eine am barock-klassischen Muster orientierte, wie auf die Modernen des späteren 19. und des 20. Jahrhunderts vorausweisende Strategie begriffen werden. Besonderes Augenmerk liegt dabei auf den Selbstzitaten, die Berlioz in “Les Troyens” verwendet, allen voran wird hier erstmals in der Forschungsliteratur die Verwendung der “idée fixe” aus der “Symphonie fantastique” in den Blick genommen.
Keywords: Musicology

Adherence to the Dutch dietary guidelines is inversely associated with 20-year mortality in a large prospective cohort study - van Lee, L; Geelen, A; Kiefte-de Jong, J C; Witteman, J C M; Hofman, A; Vonk, N; Jankovic, N; Hooft van Huysduynen, E J C; de Vries, J H M; van 't Veer, P; Franco, O H; Feskens, E J M (European Journal of Clinical Nutrition)

Michael Fischer: Religion, Nation, Krieg. Der Lutherchoral "Eine feste Burg ist unser Gott" zwischen Befreiungskriegen und Erstem Weltkrieg, Waxmann-Verlag, Münster 2014 - Janus, Richard (Jahrbuch zur Westfälischen Kirchengeschichte)

Amsterdamer Publikationen zur Sprache und Literatur (Herausgebertätigkeit von Norbert Otto Eke von Bd. 158, 2005, bis Bd. 174, 2016)
Bd. 158: Rodney Taylor: Studies on Leibnitz in German Thought and Literature 1787-1835. Berlin: Weidler 2005. 260 S. Bd. 159: Jonathan Wooley: The Ethical Project in Rolf Dieter Brinkmann’s Westwärts 1&2. Berlin: Weidler 2005. 186 S. Bd. 160: Sara Smart: The Ideal Image: Studies in Writing fort he German Court 1616-1706. Berlin: Weidler 2005. S. 370 S. Bd. 161: Teresa Ludden: ‚Das Undarstellbare darstellen’: Kulturkritik and the Representation of Difference in the works of Anne Duden. Berlin: Weidler 2006. 267 S. Bd. 162: Frank Krause: Klangbewußter Expressionismus. Moderne Techniken des rituellen Ausdrucks. Berlin: Weidler 2006. 322 S. Bd. 163: Birgit Lang: Eine Fahrt ins Blaue. Deutschsprachiges Theater und Kabarett im australischen Exil und Nach-Exil (1933-1988). Berlin: Weidler 2006. 346 S. Bd. 164: Marielle Sutherland: Images of Absence: Death and the Language of Concealment in the Poetry of Rainer Maria Rilke. Berlin: Weidler 2006. 302 S. Bd. 165: Andreas Kramer: Regionalismus und Moderne. Studien zur deutschen Literatur 1900-1933. Berlin: Weidler 2006. 409 S. Bd. 166: Marc Oliver Huber: Zwischen Schlussstrich und „Schönem Gespräch“. Erinnerung bei Thomas Mann. Berlin: Weidler 2007. 275 S. Bd. 167: Gerd Labroisse: Politisch-Historisches in literarischer Form. Zu Günter Grass’ Roman Ein weites Feld. Berlin: Weidler 2008. 310 S. Bd. 168: Svoboda Dimitrova-Moeck: Women Travel Abroad 1925-1932: Maria Leitner, Erika Mann, Marieluise Fleisser, and Elly Beinhorn. Women’s Travel Writing from the Weimar Republic. Berlin: Weidler 2009. 283 S. Bd. 169: Gregory A. Knott: Arnold Stadler: Heimat and Metaphysics. Berlin: Weidler 2009, 212 S. Bd. 170: Christian Frankenfeld: “Über jede Liebe kommt das Gesetz”. Zum Utopieschwund im Werk Thomas Braschs. Berlin: Weidler 2011. 348 S. Bd. 171: Angela Kölling: Writing on the Loose. Reading Florian Illies’s Generation Golf, Maurice G. Dantec’s Périphériques, Joschka Fischer’s Mein langer Lauf zu mir selbst, and Frédéric Beigbeder’s Windows on the World as examples of creative nonfiction. Berlin: Weidler 2012. 248 S. Bd. 172: Thorbjörn Ferber: Nationaler Antisemitismus im literarischen Realismus. Berlin: Weidler 2014. 467 S. Bd. 173: Ivo Theele: Frauen│gestalten. Inszenierte Weiblichkeit in Rainer Maria Rilkes Frühwerk. Berlin: Weidler 2015. 361 S. Bd. 174: Elias Flügge: Zimmer, Raum, Räumungen. Zur Positionierung weiblicher Figuren im ‚Privatraum‘ bei Autorinnen des 20. und 21. Jahrhunderts. Berlin: Weidler 2016. 295 S.

An Efficient Approach for the Generation of Allen Relations - Georgala, Kleanthi; Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (ECAI 2016 - 22nd European Conference on Artificial Intelligence, 29 August-2 September 2016, The Hague, The Netherlands - Including Prestigious Applications of Artificial Intelligence {(PAIS} 2016))

Towards SPARQL-Based Induction for Large-Scale RDF Data Sets - Bin, Simon; Bühmann, Lorenz; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille (ECAI 2016 - 22nd European Conference on Artificial Intelligence, 29 August-2 September 2016, The Hague, The Netherlands - Including Prestigious Applications of Artificial Intelligence {(PAIS} 2016))

6th Open Challenge on Question Answering over Linked Data (QALD-6) - Unger, Christina; Ngonga Ngomo, Axel-Cyrille; Cabrio, Elena (Semantic Web Challenges - Third SemWebEval Challenge at ESWC 2016, Heraklion, Crete, Greece, May 29 - June 2, 2016, Revised Selected Papers)

The Lazy Traveling Salesman - Memory Management for Large-Scale Link Discovery - Ngonga Ngomo, Axel-Cyrille; M. Hassan, Mofeed (The Semantic Web. Latest Advances and New Domains - 13th International Conference, ESWC 2016, Heraklion, Crete, Greece, May 29 - June 2, 2016, Proceedings)

Detecting Similar Linked Datasets Using Topic Modelling - Röder, Michael; Ngonga Ngomo, Axel-Cyrille; Ermilov, Ivan; Both, Andreas (The Semantic Web. Latest Advances and New Domains - 13th International Conference, ESWC 2016, Heraklion, Crete, Greece, May 29 - June 2, 2016, Proceedings)

Self-Assembly, Dynamics, and Polymorphism of hIAPP(20–29) Aggregates at Solid–Liquid Interfaces - Hajiraissi, Roozbeh; Giner, Ignacio; Grundmeier, Guido; Keller, Adrian (Langmuir)